2019
DOI: 10.1111/cas.14116
|View full text |Cite
|
Sign up to set email alerts
|

Different sensitivities of senescent breast cancer cells to immune cell‐mediated cytotoxicity

Abstract: Senescence is a state of growth arrest induced not only in normal cells but also in cancer cells by aging or stress, which triggers DNA damage. Despite growth suppression, senescent cancer cells promote tumor formation and recurrence by producing cytokines and growth factors; this state is designated as the senescence‐associated secretory phenotype. In this study, we examined the susceptibility of senescent human breast cancer cells to immune cell‐mediated cytotoxicity. Doxorubicin (DXR) treatment induced sene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Before the assays, T cells were in vitro expanded after 2 days of culture in anti–CD3 antibody‐coated wells with 300 U/mL IL‐2 and then with IL‐2 alone for 7‐10 days. Although the in vitro expanded CAR‐T cells were unexpectedly positive for CD4, 14 we performed experiments using these activated T cells. The percentages of apoptotic cancer cells were examined by flow cytometry by gating CD45‐negative cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the assays, T cells were in vitro expanded after 2 days of culture in anti–CD3 antibody‐coated wells with 300 U/mL IL‐2 and then with IL‐2 alone for 7‐10 days. Although the in vitro expanded CAR‐T cells were unexpectedly positive for CD4, 14 we performed experiments using these activated T cells. The percentages of apoptotic cancer cells were examined by flow cytometry by gating CD45‐negative cells.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, they exerted higher levels of cytotoxicity against PEM‐treated PC9 and A549 cells than against untreated cancer cells. In terms of the underlying mechanism, we recently reported that these activated CD4 + T cells showed enhanced cytotoxicity against doxorubicin‐treated human breast cancer cells partially through the tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL)/death receptor system 14 . This apoptosis‐inducing system may be involved in augmenting the sensitivity of PEM‐treated NSCLC cells to cytotoxic immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…These events allow the functional trans-presentation of IL-15 to neighboring NK cells leading to NK cell recognition and cytotoxicity [ 194 ]. Moreover, additional NK mechanisms such as antibody-dependent cellular cytotoxicity (ADCC) are activated after chemotherapy to eliminate senescent breast cancer cells, where doxorubicin enhances senescence through SASP secretion leading to a perforin-dependent increase in ADCC by NK cells [ 195 ].…”
Section: Clinical Relevance Of Senescence In Immunotherapy: a Balamentioning
confidence: 99%
“…Those results were partially confirmed by Huun and co-workers in MCF-7 cells as well as via other authors (in vitro and in vivo models) since only concomitant inactivation of P53 and RB genes led to a decrease of the senescent cells numbers [ 26 , 27 , 28 , 29 ]. Studies on p53-mutated MDA-MB-231 and BT-549 cells revealed that doxorubicin-induced senescence led to an increased expression level of p 21 and p16, respectively [ 25 , 30 ].…”
Section: Senescence and Anticancer Strategymentioning
confidence: 99%
“…Matrix enzymes can remodel the microenvironment to promote cancer initiation and development. Some SASP proteins, e.g., cytokines and THBS1, act in maintenance of senescence [ 23 , 29 , 30 , 86 , 94 ].…”
Section: Senescence Induction As a New Anticancer Strategymentioning
confidence: 99%